DETERMINANT OF TAX AUDIT QUALITY WITH AUDIT ENVIRONTMENT AS MEDIATORS - Rio Eryco Vebriadi; Sabaruddin Sabaruddin (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the determinants of tax audit quality by integrating input, process, and output factors with environmental context as a mediating variable. Data were collected from 129 tax auditors in Jakarta using structured questionnaires and analyzed through PLS-SEM. Results indicate that all factors significantly influence audit quality, with environmental factors showing the strongest effect and acting as a partial mediator. These findings highlight the importance of regulatory clarity and organizational culture in strengthening technical and procedural components, offering practical insights for improving tax audit quality and compliance.